Prescribing vitamins at primary health care level: Exploration of facts, factors and solution - Das, Adhir Kumar; Rahman, Md. Sayedur (Bangladesh Journal of Pharmacology, 2011)
The impact of educational intervention on prescribing trend of vitamins at primary health care level was investigated by analyzing 2000 prescriptions containing vitamins. Prevalence of vitamin prescribing was 30.16%, 38.69% and 45.35% and contribution of vitamins in the cost of drugs prescribed in vitamin containing prescription was 27.58%, 30.40% and 41.85% at Upazilla Health Complexes (UHC), non-government organizations (NGO) and private practices (PP) respectively. Both parameters significantly (p<0.001) decreased after intervention. Prescribing of single vitamin preparations was 3.75%, 13.87% and 7.75% and appropriateness of the vitamin prescribing was 14.63%, 24.13% and 14.75% at UHC, NGO and PP respectively. Both parameters significantly (p<0.001) increased after intervention. Negligible emphasis on vitamin in pharmacology teaching at MBBS level was observed. Dependency on promotional materials of manufacturers were changed after intervention. In conclusion, knowledge deficiency due to inadequate professional training and dependency on biased information perhaps contributed in irrational prescribing of vitamins.